Analysis of The Implementation of Smart Governance through Twitter in Local Governments in Indonesia - Iman Surya; Niken Nurmiyati; Suranto Suranto; Nur Hasanah (Jurnal Administrasi Publik (Public Administration Journal), 2021)
The research entitled "Analysis of the Implementation of Smart Governance through Twitter in Local Governments in Indonesia" is a study that focuses on the analysis of branding, criticality, participation, and transparency. This study aims to find out about the use of Twitter in Government. This research is qualitative research using artificial-intelligent software NVivo 12 Plus. The results showed that the function of branding in the health sector in Central Java dominated, followed by DKI Jakarta, Bandung City, and Surabaya City. The superior crisis function is the health crisis with the highest position, namely Central Java, Bandung City, DKI Jakarta, and Surabaya City. The participation function superior in terms of public engagement is DKI Jakarta; the participation function in the superior collaboration field is the City of Surabaya, Bandung City, and Central Java. The function of transparency in terms of superior service is DKI Jakarta, Surabaya City, Central Java, and Bandung City.